Excess of Serotonin (5-HT) Alters the Segregation of Ispilateral and Contralateral Retinal Projections in Monoamine Oxidase A Knock-Out Mice: Possible Role of 5-HT Uptake in Retinal Ganglion Cells During Development - Upton, A. L. (J Neurosci, 1999)
Retinal ganglion cell (RGCs) project to the ipsilateral and contralateral sides of the brain in the dorsal lateral geniculate nucleus (dLGN) and the superior colliculus (SC). Projections from both eyes are initially intermingled until postnatal day 3 (P3) but segregate into eye-specific layers by P8. We report that this segregation does not occur in monoamine oxidase A knock-out mice (MAOA-KO) that have elevated brain levels of serotonin (5-HT) and noradrenaline. The abnormal development of retinal projections can be reversed by inhibiting 5-HT synthesis from P0 to P15. We found that in MAOA-KO mice, 5-HT accumulates in a subpopulation of RGCs and axons during embryonic and early postnatal development. The RGCs do not synthesize 5-HT but reuptake the amine from the extracellular space. In both MAOA-KO and normal mice, high-affinity uptake of 5-HT and serotonin transporter (SERT) immunoreactivity are observed in retinal axons from the optic cup to retinal terminal fields in the SC and dLGN. In the dLGN, transient SERT labeling corresponds predominantly to the ipsilateral retinal projection fields. We show that, in addition to SERT, developing RGCs also transiently express the vesicular monoamine transporter gene VMAT2: thus, retinal axons could store 5-HT in synaptic vesicles and possibly use it as a borrowed neurotransmitter. Finally we show that the 5-HT-1B receptor gene is expressed by RGCs throughout the retina from E15 until adult life. Activation of this receptor is known, from previous studies, to reduce retinotectal activity; thus 5-HT in excess could inhibit activity-dependent segregation mechanisms. A hypothesis is proposed whereby, during normal development, localized SERT expression could confer specific neurotransmission properties on a subset of RGCs and could be important in the fine-tuning of retinal projections.